2001
DOI: 10.1128/jcm.39.5.1889-1894.2001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Pulsed-Field Gel Electrophoresis Protocol for Subtyping of Campylobacter jejuni

Abstract: We developed a rapid pulsed-field gel electrophoresis (PFGE) protocol for subtyping Campylobacter isolates based on the standardized protocols used by PulseNet laboratories for the subtyping of other food-borne bacterial pathogens. Various combinations of buffers, reagents, reaction conditions (e.g., cell suspension concentration, lysis time, lysis temperature, and restriction enzyme concentration), and electrophoretic parameters were evaluated in an effort to devise a protocol that is simple, rapid, and robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
242
0
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(250 citation statements)
references
References 19 publications
0
242
0
8
Order By: Relevance
“…Preparation of Campylobacter DNA was performed by the Pulsenet protocol (Ribot et al, 2001). PFGE by SmaI (Roche) was also performed by the Pulsenet protocol and by KpnI (Takara, Conda, Madrid, Spain) using the protocol of On et al (1998).…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of Campylobacter DNA was performed by the Pulsenet protocol (Ribot et al, 2001). PFGE by SmaI (Roche) was also performed by the Pulsenet protocol and by KpnI (Takara, Conda, Madrid, Spain) using the protocol of On et al (1998).…”
Section: Methodsmentioning
confidence: 99%
“…The first molecular methods to be used extensively, such as pulse field gel electrophoresis (PFGE) fingerprinting and serotyping, showed that Campylobacter in clinical samples were highly diverse comprising the two common species with numerous subtypes within them (Frost et al 1998;Ribot et al 2001). However, the most influential advances in understanding the evolutionary forces that shape this complex population arose from the development and application of multilocus sequence typing (MLST) (Maiden et al 1998), which enabled evolutionary and population genetic analyses to be applied to isolate characterization data.…”
Section: The Impact Of Sequence-based Molecular Typingmentioning
confidence: 99%
“…The CDC uses this method in their PulseNet system (41,46). The Dice correlation (10) considers the presence or absence of PFGE bands that have been identified in the fingerprints to create the correlation matrix used by the UPGMA algorithm (45).…”
Section: Vol 42 2004 Assessment Of Flow Cytometry and Gel Electrophmentioning
confidence: 99%